Analyzing the Transaction Costs of Cocoa (Theobroma cacao) Grown in Southern Córdoba, Colombia - Martínez-Reina, Antonio María; Tordecilla-Zumaqué, Lilibet; Rodríguez-Pinto, María del Valle; Grandett-Martínez, Liliana María; Díaz-Cabadíaz, Abelardo; Ballesteros-Leal, Henry Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The lack of knowledge in economic analyses related to transaction costs for cocoa production in the department of Córdoba determined that this work objective was to identify and analyze which variables have the greatest impact on the cocoa farmers of Córdoba on their transaction costs. Based on a survey of 158 farmers selected at random from the municipalities of Montelíbano, Puerto Libertador, Tierralta and Valencia, the influence exerted by the association, the cost of transportation, the state of the road and the distance to the sales sites, was determined using descriptive statistics and a logit model. The elements that had the greatest impact on transaction costs were the distance to the point of sale and the condition of the roads, mainly for Puerto Libertador, which had the greatest distance and the worst condition of the roads. Furthermore, a relevant effect was found on the part of the associations in the information that determines the price and zero supervision costs due to cash payment in the commercialization of cocoa.